IN SEARCH OF A THEORETICAL FRAMEWORK TOWARDS INTERCULTURAL AWARENESS AND TOLERANCE - Westhuizen, M. A. van der (Scriptura, 2015)
Even if legalised segregation (i.e. Apartheid) has ceased, individuals, groups and communities remain sensitive owing to past experiences. Furthermore communication obstacles lead to on-going misunderstandings that result in mistrust (Williams, 2002:51-67). Without a process to stimulate intercultural awareness and tolerance, the legacy of the past cannot be undone. The question therefore is: How can we approach intercultural misunderstanding and mistrust so as to find a way to work towards intercultural awareness and tolerance? The aim of this contribution has been to identify a theoretical framework that could pave the way to finding practical ways of addressing the remaining misunderstandings and mistrust in present-day South Africa. The authors, working from a trans-disciplinary framework, first did a review of the literature in search of a theoretical framework. The contribution concludes with a proposed theoretical framework and some recommendations for further exploration of this topic.